Influence of media learning strip story to improve memorization of mufrodat students in class x at MAN 2 Ciamis - Nurdiana, Ryan; Farhani, Cecep (Maliki Interdisciplinary Journal, 2024)
All efforts to improve students’ memorization can be done with strip story media so that students will change the pattern of inactive learning activities and teachers to use the media, in order to foster superior motivation and interest in learning. In this study, the focus is on the media strip story which is used to improve students’ memorization skills. This study uses an experiment that is quantitative in its data using numbers. Meanwhile, for data collection by observation, pretest and posttest questionnaire tests with the experimental group in the class. The results of the research, that there is an effect of learning strip story media to improve the memorization of mufrodat students in class X at MAN 2 Ciamis. In this case, it shows the experimental class with learning using strip story media by obtaining an n-gain score with a "Medium" level with an average value of 0.56. While the results of the N-gain value in the control class get the ’Medium’ category (Slightly higher than the experimental class value) with an average of 0.64. Thus, the Strip Story learning media is effective for use in learning Arabic.